2013
DOI: 10.14569/ijacsa.2013.041108
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory study of proposed factors to Adopt e-government Services

Abstract: Abstract-this paper discusses e-government, in particular the challenges that face adoption of e-government in Saudi Arabia. In this research we define e-government as a matrix of stakeholders: governments to governments, governments to business and governments to citizens, using information and communications technology to deliver and consume services. egovernment services still face many challenges in their implementation and general adoption in many countries including Saudi Arabia. In addition, the backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Alateyah, Crowder and Wills [48] examined challenges that face adoption of e-Government in Saudi Arabia. The study has identified the influential factors that affect the citizens' intention to adopt e-Government services in Saudi Arabia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alateyah, Crowder and Wills [48] examined challenges that face adoption of e-Government in Saudi Arabia. The study has identified the influential factors that affect the citizens' intention to adopt e-Government services in Saudi Arabia.…”
Section: Literature Reviewmentioning
confidence: 99%